Artificial intelligence in university programs in Ecuador: a case study at the Technical University of Manabí - Castro Bermúdez, Esther; Mawyin Cevallos, Francisco Antonio; Guerrero Aray, Gabriela Rossana (Scripta Mundi, 2026)
Information literacy is a fundamental pillar of contemporary higher education, especially when integrated with formative research processes aimed at developing critical thinking and autonomous learning. At the Technical University of Manabí (UTM), the incorporation of artificial intelligence (AI) into university programs presents challenges related to its pedagogical integration, equitable access to technological resources, and faculty preparation for its effective use in teaching. In this context, this study aimed to characterize the integration of AI into UTM's university programs based on its implementation methods and the levels of appropriation by faculty and students. Methods and techniques were employed at both theoretical and empirical levels, with a focus on document analysis, which was used to examine curricula, academic programs, and institutional documents related to educational innovation. The results revealed an initial and heterogeneous integration of AI, with more established experiences in technical fields and limited ones in the social sciences and humanities. Furthermore, a growing willingness among faculty and students to use AI was identified, although gaps remain in critical and pedagogical training. It is concluded that strengthening information and digital literacy skills is essential to promoting the reflective and sustainable use of AI in university education.
Keywords: artificial intelligence; higher education; research ethics